Home Fire Safety Checks in New South Wales: an economic evaluation of the pilot program. Issue 8 (3rd August 2018) - Tannous, W. Kathy; Whybro, M.; Lewis, C.; Broomhall, S.; Ollerenshaw, M.; Watson, G.; Fish, C.; Franks, E.
Abstract : Traumatic events such as fire can result in fatality, injury, and loss of property; even a minor fire can interrupt the normal flow of people's lives. During the years 2009–2013, urban and regional New South Wales (NSW) experienced an annual average of 4329 residential structural fires with 593 injuries and 22 fatalities at an annual cost of $656 million dollars. In 2014, Fire and Rescue NSW piloted a program called Home Fire Safety Checks (HFSC), aimed at high-risk households. In total, 228 homes in 8 suburbs received safety checks, including having smoke alarms installed, having batteries changed in smoke alarms, and being provided with fire blankets and fire safety information. The pilot study design enabled detailed economic evaluation of the program, including both development costs and ongoing costs for a full roll-out. Analysis of the cost of fire within NSW, combined with measurements of the success of similar programs internationally, demonstrates the program's cost effectiveness. Savings per dollar spent exceed $12 if the program includes 1% of high-risk homes and obtains a 0.75% reduction in number of fires. These results demonstrate that a full roll-out of the HFSC program warrants ongoing funding. External factors affecting program delivery include community acceptance and willingness to participate in the program, particularly very high-risk individuals, and ongoing behavioral change. In addition, HFSC faces the same ongoing funding challenges other preventative community programs face in a period of tightening state budgets.